2009
DOI: 10.1002/jmv.21404
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between human papillomavirus type 5 E2 and polo‐like kinase 1

Abstract: The E2 protein of the papillomavirus plays an essential role in the viral life cycle. Through a yeast two-hybrid screening, human polo-like kinase 1 was found to interact with human papillomavirus type 5 E2. Further characterization identified that the domains responsible for the interaction are the transactivation domain of HPV-5 E2 and the sequence between the kinase and the polo box domains of Plk1. In vivo, Plk1 and HPV-5 E2 are colocalized at the nuclear speckles. In the skin epithelium not infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This suggests that SRPK1 phosphorylation may have a role in regulating the cellular localization of HPV1 E2. Indeed, SRPK1 activity is associated with the release of HPV5 E2 from nuclear speckles and transport to the cytoplasm (42,43). Since E2 stability is sensitive to phosphorylation (44), an alternative explanation is that SRPK1 phosphorylation of the E2 hinge regulates the stability of the fraction of E2 protein that is located within the nucleolus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that SRPK1 phosphorylation may have a role in regulating the cellular localization of HPV1 E2. Indeed, SRPK1 activity is associated with the release of HPV5 E2 from nuclear speckles and transport to the cytoplasm (42,43). Since E2 stability is sensitive to phosphorylation (44), an alternative explanation is that SRPK1 phosphorylation of the E2 hinge regulates the stability of the fraction of E2 protein that is located within the nucleolus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HPV5 E2 hinge region contains 27 RS/SR motifs. The HPV5 E2 protein has been shown to be a substrate for SRPK1 in vitro, and evidence suggests that this phosphorylation is restricted to the hinge region (42,43). Examination of the sequence of the HPV1 E2 hinge region identified four RS/SR dipeptide motifs, with the serines at positions 265, 267, 281, and 306 (Fig.…”
Section: Hpv1 E1^e4 Inhibits Srpk1 Phosphorylation Of Cellular Srmentioning
confidence: 97%
“…PLK1-mediated P protein phosphorylation downregulates viral gene expression and thereby avoids efficient induction of the host innate immune response [34]. Furthermore, the interaction of the E2 protein of human papillomavirus type 5 with PLK1 was reported to inhibit Brd4 phosphorylation by PLK1, thereby interfering with cellular functions of Brd4 in promoting cell cycle progression from the G1 to the S phases [35]. Finally, binding of PLK1 to the NS5A protein of hepatitis C virus and its hyperphosphorylation by PLK1 is important for efficient virus replication [36].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the hinge of HPV8 E2 is highly phosphorylated, and the majority of this phosphorylation is likely to be of the many SR/RS dipeptides located here . SRPK1 can phosphorylate the hinge region of HPV5 and HPV8 E2 proteins in vitro . Prescott et al.…”
Section: Resultsmentioning
confidence: 89%